1992
DOI: 10.3109/10799899209074800
|View full text |Cite
|
Sign up to set email alerts
|

A Low Affinity Vasopressin V2-Receptor in Inherited Nephrogenic Diabetes Insipidus

Abstract: Congenital nephrogenic diabetes insipidus (NDI) is an X-linked inherited disorder characterized by renal resistance to the antidiuretic hormonal action of vasopressin. This study describes the molecular basis of nephrogenic diabetes insipidus in a dog family. Kidney membranes prepared from NDI-affected male huskies were examined for vasopressin binding and response. Compared to membranes from unaffected canines, those from the kidney inner medulla of NDI-dogs possessed normal V2-receptor numbers, but with 10-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
3
3
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 10 publications
0
11
0
Order By: Relevance
“…We presented several illustrative examples such as the presence of the SLiM DOC_MAPK_1 in the kangaroo rat AVPR2, which mediates docking with a kinase involved with cellular response to a diverse array of stimuli including osmotic stress (Pearson et al , 2001). This unique characteristic among placental mammals might have adaptive implications, since the importance of AVPR2 in the hypothalamic-renal regulation of water and electrolyte homeostasis became evident when mutations in the AVPR2 gene were associated with nephrogenic diabetes insipidus in humans, mice, dogs, and horses, a disease characterized by polyuria and polydipsia (Luzius et al , 1992; Böselt et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…We presented several illustrative examples such as the presence of the SLiM DOC_MAPK_1 in the kangaroo rat AVPR2, which mediates docking with a kinase involved with cellular response to a diverse array of stimuli including osmotic stress (Pearson et al , 2001). This unique characteristic among placental mammals might have adaptive implications, since the importance of AVPR2 in the hypothalamic-renal regulation of water and electrolyte homeostasis became evident when mutations in the AVPR2 gene were associated with nephrogenic diabetes insipidus in humans, mice, dogs, and horses, a disease characterized by polyuria and polydipsia (Luzius et al , 1992; Böselt et al , 2009). …”
Section: Discussionmentioning
confidence: 99%
“…DDAVP has been shown to be more effective in the patient with congenital diabetes insipidus with reduced renal blood flow and a partial vasopressin response. NDI-affected dogs have been shown to exhibit an antidiuretic response to very high doses of V2-specific agonists, consistent with their possessing V2 receptors of low affinity [12]. Inaba et al [7]reported that the binding capacity and maximum cAMP accumulation of R104C with COS-7 cells decreased by 10 and 50% of wild type, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…NDI is characterized by the inability to concentrate the urine and an increased urine volume. Inherited NDI is not only found in humans but also in mice, dogs and horses [14][16] indicating similar functional relevance of the V2R among mammals. However, there are several examples where patients managed NDI basically by appropriate water supply (family 4 in [17] and family 1 in [18]).…”
Section: Introductionmentioning
confidence: 91%